An improved method to efficiently acquire rice black-streaked dwarf virus viruliferous small brown planthoppers - Du, Linlin; Zeng, Bo; Li, Xuejuan; Lan, Ying; Guo, Wei; Wang, Zhaoyun; Liu, Zhiyang; Zhou, Yijun; Jiban, Kumar Kunda; Zhou, Tong (Frontiers Media, 2023)
Accurate phenotypic identification is the basis of research for resistance genetics and rice breeding for resistance to RBSDV disease. Obtaining rice black-streaked dwarf virus (RBSDV) viruliferous small brown planthoppers (SBPHs) with high transmission efficiency is an essential part of accurate phenotypic identification. Here, through quantifying number of RBSDV copies in infected rice plants, optimizing times of SBPHs fed on RBSDV-infected rice plants and leaf stage of rice seedlings, a method to acquire an RBSDV-carrying SBPH population more efficiently was improved. The results showed that rate of viruliferous SBPHs was significantly higher when fed on RBSDV-infected rice plants that had the copy numbers of RBSDV S10 of 3.0*104 and 1.1*104 than 8.3*102. Therefore, it is more efficient for SBPHs to acquire the virus when fed on RBSDV-infected rice plants that have copy numbers of RBSDV S10 above 1.1*104. The rate of viruliferous SBPHs were 50% and 54%, respectively, after the insects fed on RBSDV-infected rice plants for 7 and 9 days and being transferred to healthy rice seedlings for 5 and 3 days, which was significantly higher than those at other feeding times. The optimal inoculation leaf stage of rice seedlings was the 2-3-leaf stage (3 effective SBPHs per seedling for 72 h), but a high rate of viruliferous SBPHs may be suggested for inoculation of older rice seedlings.